The Effect of Training and Education Programs to Develop HospThe Effect of Training and Education Programs on Developing Hospital Employees’ Competency at the Inpatient Uniital Employees’ Competency - Era Resna; Haninun Haninun (Penerbit Goodwood, 2026)
Purpose: Human resources are critical determinants of hospital service quality, particularly in inpatient units that require continuous care, clinical accuracy, and effective coordination. Competency gaps may arise from rapid technological changes, evolving service standards, and limited structured training, negatively affecting performance, service quality, and patient satisfaction. This study analyzes the influence of training and education on employee competency development in the inpatient unit of RS Bintang Amin Bandar Lampung, grounded in Human Capital Theory, with training and education as independent variables and competence as the dependent variable. Methodology/approach: A quantitative design was employed, with questionnaires distributed to 100 inpatient employees selected using accidental sampling method. Data were analyzed using multiple linear regression, supported by validity and reliability testing, and partial (t-test) and simultaneous (F-test) hypothesis testing. Results: Training and education have positive and significant effects on employee competence, both individually and simultaneously. Conclusions: Structured and continuous training and education programs are essential investments for enhancing competence and improving inpatient service quality. Limitations: The study is limited to a single hospital inpatient unit and uses non-probability sampling, which restricts generalizability, although it offers empirical support for the importance of continuous training. Contributions: This study reinforces the application of Human Capital Theory in healthcare and provides practical guidance for hospital human resource development strategies.